مدى حاجة طلاب الجامعة لخدمات المرشد النفسي بالكليات الجامعي من وجهة نظر الطلاب (Comprehensive Journal of Science, 2026)
This research aims to identify the extent of university students' need for psychological counseling services and whether there are statistically significant differences based on gender and academic specialization. The researchers used a descriptive methodology and a simple stratified sampling method, employing a questionnaire as the data collection tool. This approach was based on previous studies and the theoretical framework of this research. The sample consisted of (40) male and female students, as detailed in the table.The research findings indicate that university students have a definite need for psychological counseling services in university institutions. However, no statistically significant differences were found based on gender or academic specialization in the extent of this need